IMPLEMENTACIÓN Y FUNCIONAMIENTO DE LA CAJA DE AHORRO Y CRÉDITO PARA LA FEDERACIÓN DEPORTIVA DE LIGAS BARRIALES DE LOJA, FEDELIBAL - Álvarez Pasaca, Francis Javier (2017)
The present thesis consists in realizing a feasibility project for the Implementation of the Savings and Credit Fund for FEDELIBAL; for which the market, technical, administrative - legal, financial economic and financial evaluation studies were carried out. The paper considers a projective methodology in which the Deductive, Inductive, and Analytical Method was used. Techniques used as direct observation, interview with Ing. Edwin Guerrero Jiménez president of FEDELIBAL, the survey, was applied to the presidents of clubs that are partners of FEDELIBAL. The market study, refers to the collection and analysis of data and information about customers, competitors and the market. In the technical study, its macro and microlocalization, the capacity and distribution of the project were defined. The administrative study, to determine its organizational structure, organizational charts, manual of functions; the financial study, to know the costs and expenses, project income, financial evaluation of the project, analyzing the IRR, VAN, B / C, PRC, SENSITIVITY ANALYSIS, and on this basis and having positive values was determined the feasibility of the same. Once obtained the previous results, it is concluded that the feasibility project, economically feasible, which makes it necessary to create the box.